PENGAWETAN KAYU KARET,AGATHIS, DAN TUSAM DENGAN METODE TEKANAN BERGANTI - Barly Barly; Pipin Permadi (Jurnal Penelitian Hasil Hutan, 1989)
The  paper  deals  with  an experiment    of  alternating  pressure  method   on  three  wood  species  with  borax.    The  green wood  samples  were  impregnated   with  three percent   borax  solution.   The  results  of  experiment    are as follows  :1.  Wood species  and  treatment   schedule  show  non  significant    effect   on  boron  penetration     and  retention.2.  In  general  the  impregnation  of   the  green  wood  results  in  variable  treatment   and  limited  penetration   and  retention.3.  Retention  and  penetration    showed   better   figures  when  only   modifying    the  treating  cycle   rather  than  using  a  pretreatment.